REPRESENTATION OF REFERNTIAL SITUTIONS IN ENGLISH LITERARY TEXT AND ITS TEMPORAL COMPONENT AS EXPRESSION OF THE SPEAKER’S INNER-TIME CONSCIOUSNESS - Bekmirzayeva , Dilrabo Olimjonovna (Innovative Development in Educational Activities, 2023)
The goal of this work is to convey the information about refential situation in English language. The categories of tense, aspect, and perfect of the English verbal forms used in speech are the main focus of the study since they express the temporal aspect of the linguistic consciousness of the speaker. The examination of the phenomenological theory of intentionality introduces the idea of inner-time consciousness as the underlying idea for all signitive intentions. The linguistic signs are viewed as tools for expressing and reconstructing the mental representations of the speaker that comprise up temporal sense.